Patterns in Aggregated Human Conflict Behaviour: Spectral analyses reveal 7- and 29-day periodicities reflecting weekly and monthly lunar cycles - Tessaro, Lucas (Advances in Social Sciences Research Journal, 2019)
Previous works demonstrated that human creative output fluctuates in periods of 500-years, and more importantly that these periods of creative output maxima occurred simultaneous with increased solar activity. Indeed, early works by Chizhevskiy pointed to the correlation between solar-and-lunar geophysical variables and human behaviour. Interestingly, Persinger, and St. Pierre demonstrated increased aggression in rats during increased geophysical activity. Using these studies as a foundation, we explored the CDB90 Battle Dataset to find a pattern or potential periodicity in large scale human aggressive behaviour – war – specifically within the duration of battles. Using the mean duration of battles for various wars from 1600 to 1950 revealed a 7-day periodicity in military conflicts during the 20th Century, with subharmonics at 14, 22, and 29-days. The existence of the 7-day period in large-scale aggregate behaviour may suggest the reflection of biological cycles also of 7-days, whose original entrainment is likely due to solar and lunar influences. Such entrainment may be why attempts to organize human societies with cycles other than 7-days become superseded by circaseptan systems as they reflect a natural, biological pattern.